Testing Contemporary Functionals and Basis Sets for their Accuracy in Predicting Vibrational Modes of Newly Discovered Alkaline Earth Metals-Carbonyl Complexes - Bhadoria P.; Mishra B.K.; Ramanathan V. (My University, 2025)
Harmonic and anharmonic normal modes were computed for the alkaline earth metal carbonyl complexes, namely Ba(CO)+, Ba(CO)-, Ba(CO)2, Ca(CO)2, Ba(CO)3, and Ba(CO)4, using various DFT functionals and methods in combination with three different basis sets (cc-pVTZ-DK3, cc-pVTZ-DK2 cc-pVTZ-X2C, and def2-TZVPP for Ba and Ca atoms). Divergent results were observed among these systems for the carbonyl stretching mode. This study underscores the inadequacy of the current computational methods, ongoing need for a comprehensive understanding of these newly synthesized carbonyl complexes and the development of a benchmark method that can effectively address the vibrational frequencies of all these systems. © 2024 National Institute of Science Communication and Policy Research. All rights reserved.